Evaluasi Penerapan PSAK No 16 dalam Penyesuaian dan Perlakuan Akuntansi Aset Tetap Perusahaan XXX (Studi Kasus Pada Perusahaan yang Bergerak di Bidang Kesehatan) - Rahmadlani Afiful Amsyi; Sjarief Hidajat (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to find out whether the preparation of financial reports in the fixed assets section that has been prepared by the accountant of company XXX (engaged in the health sector) has been prepared in accordance with the regulations in PSAK No. 16 or not. The data obtained for this research was by using a qualitative case study method with data collection techniques obtained by requesting data through observation, interviews and documentation. The expected achievement of the results of analyzing the data that has been processed is to find conclusions regarding the evaluation of the application of PSAK No. 16 in the adjustment and treatment of a company's fixed assets. The conclusion obtained from the data processing results of the methods that have been carried out is that it concludes that the financial records made by the accounting department in accounting for the final report results in the fixed assets section of PT XXX in carrying out its activities are guided by the policies that lead to PSAK No. 16. However, the facts in the field after the results of data processing were found to be that company accountants had not fully implemented it properly, it was found that there were still several things that had been missed, for example, the lack of attention by accountants to re-examination of revaluation (asset revaluation), to the results presented in prepared financial reports as well as adjustments to the useful life of fixed assets owned if discrepancies are found in the results of calculating the useful life obtained with the total accumulated results.